Dissecting the Political Persona of the 2024 Indonesian Presidential Election through Visual Framing Analysis - Muhammad Dicka Ma'arief Alyatalatthaf; Altobeli Lobodally; Natalia Faradheta Putri (Profetik: Jurnal Komunikasi, 2024)
Public interest in political battles is constant, and the Indonesian presidential election in February 2024 is no exception. The three presidential candidates, who have been declared, aggressively establish their political personas and gain exposure and notoriety using Instagram, including @aniesbaswedan, @ganjar_pranowo, and @prabowo. This study aims to dissect the political persona of the 2024 Indonesian presidential candidates using the visual framing analysis method, studying how certain points of view are emphasized or made prominent through visual messages. While other framing studies focus on textual analysis, visual framing analysis is rarely employed even though visual elements have the power to build emotional affection and can last longer in memory. The study's data set comprises Instagram posts from the officially declared presidential contender (@aniesbaswedan from October 3, 2022; @ganjar_pranowo from April 21, 2023; @prabowo from August 12, 2022) to May 21, 2023. The research findings indicate that the political persona built by each presidential candidate still revolves around aspects of their own inherent identity such as religion, race, ethnicity, tribe, customs, habits, education level, economic status, social status, family background, and political stance, rather than providing a clear picture of their priority policy programs when in office.